A cross-sectional study on maternal anxiety levels after cytomegalovirus screening. (2nd July 2020) - Uehara, Kanako; Kaneko, Masatoki; Matsuoka, Ayaka; Kuroki, Mana; Minematsu, Toshio
Abstract: Purpose: we aimed to estimate the anxiety levels of pregnant women following maternal serum screening for CMV infection. Materials and methods: In this case-control study conducted from April 2016 to June 2017, we enrolled all pregnant women referred to our hospital who were CMV immunoglobulin (Ig) M antibody positive (IgM-positive group, n = 51); further, those who were CMV IgG positive but IgM negative (IgM-negative group, n = 51) during the same period were included as study controls. Data were collected on patient characteristics, CMV IgM levels, and whether patients were accompanied by their partners during the first hospital visit after CMV IgM testing. The State-Trait Anxiety Inventory was used to assess anxiety levels. Results: Both groups were age matched [mean age (years): IgM-positive, 30 ± 4.2 and IgM-negative, 29.9 ± 4.6]. The mean state-anxiety score was higher in the IgM-positive group (53 ± 9.6) than in the IgM-negative group (38.5 ± 7.0, p < .05) with no between-group differences in trait-anxiety scores. Similarly, a higher number of women were accompanied by their partners in the IgM-positive group. The state-anxiety scores and CMV IgM levels were not correlated in the IgM-positive group. Conclusion: Counseling support is essential for IgM-positive pregnant women following serum screening, and the screening should be avoided if support systems are unavailable.